2021
DOI: 10.1002/advs.202100583
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Plasmonic Biosensor with Tetrahedral DNA Nanostructure as Carriers for Label‐Free and Ultrasensitive Detection of miR‐155

Abstract: MicroRNAs play an important role in early development, cell proliferation, apoptosis, and cell death, and are aberrantly expressed in many types of cancers. To understand their function and diagnose cancer at an early stage, it is crucial to quantitatively detect microRNA without invasive labels. Here, a plasmonic biosensor based on surface‐enhanced infrared absorption (SEIRA) for rapid, label‐free, and ultrasensitive detection of miR‐155 is reported. This technology leverages metamaterial perfect absorbers st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 64 publications
(45 reference statements)
0
28
0
Order By: Relevance
“…The TEM images in Figure B,C show the m-TDN nanostructure with a typical size and morphology of a tetrahedral DNA. The AFM images and force–distance curves in Figure D,E show the m-TDN nanostructure with the typical morphology and height of the DNA tetrahedron could be observed; additional AFM images can be found in Supporting Information. The results demonstrated the successful fabrication of m-TDN as well.…”
Section: Resultsmentioning
confidence: 99%
“…The TEM images in Figure B,C show the m-TDN nanostructure with a typical size and morphology of a tetrahedral DNA. The AFM images and force–distance curves in Figure D,E show the m-TDN nanostructure with the typical morphology and height of the DNA tetrahedron could be observed; additional AFM images can be found in Supporting Information. The results demonstrated the successful fabrication of m-TDN as well.…”
Section: Resultsmentioning
confidence: 99%
“…[172,173] These SEIRA-based nanophotonic platforms have realized EFs of 10 4 -10 7 [166,174] for biomolecular detection, enabled by the coupling between the enhanced nearfields of the resonators and the vibrational modes of the target molecules. In the following, we will highlight several recent nanophotonic SEIRA platforms with great potential for fluidic integration toward real-time optofluidic sensing, focusing on Fabry-Pérot (FP) optical cavities, [175,176] MPAs, [177,178] and all-dielectric metasurfaces based on photonic quasi-BICs. [179,180] Conceptually, a coaxial aperture with a diameter on the order of micrometers and a sub-10 nm gap can be designed to support a zeroth order FP resonance in the mid-IR region, [181] where the incident light couples into ultranarrow annular nanogaps (Figure 3f).…”
Section: Surface-enhanced Infrared Absorption Spectroscopy (Seiras)mentioning
confidence: 99%
“…[185][186][187] By combining a plasmonic MPA chip with tetrahedral DNA nanostructures, Hui et al have demonstrated ultrasensitive quantification of microRNA molecules with very high sensitivity and an extremely low detection limit of 0.1 × 10 −12 m, which is about 100 times lower than that of previously used fluorescence-based detection methods. [177] Importantly, to achieve compact and portable diagnostic devices, there is a need for reducing the size of the nanoantennas while simultaneously targeting vibrational bands in a wide spectral range, which requires methods for precisely tuning the antenna resonances through nanometer-scale size vibration. Using Fabry-Pérot modes in nanostructured metal-insulator-metal (MIM) resonators, Yoo et al showed that the resonances could be readily tailored within sub-10 nm insulator gaps for SEIRA through atomic layer lithography.…”
Section: Surface-enhanced Infrared Absorption Spectroscopy (Seiras)mentioning
confidence: 99%
“…Therefore, MEMS-/NEMS-based sensors have always been an important part of wireless sensor networks. [35][36][37] Notably, the wireless sensor network would require a large number of batteries to power those massive and distributed sensors. Therefore, it is very important to establish a sustainable wireless IoT sensing system by developing energy harvesters and self-powered sensors based on specific scenarios.…”
Section: Introductionmentioning
confidence: 99%